Dynamic charge modulate lithium uniform plating functional composite anode for dendrite-free lithium metal batteries. (November 2022) - Zhang, Wendi; Fan, Qianxiao; Zhang, Dongmei; Liu, Lehao; Liu, Shen; Fang, Zhengyuan; Li, Wei; Li, Xiaodan; Li, Meicheng
Abstract: Lithium metal is considered as the 'sharp blade' to break through the limitation on energy density of lithium batteries. However, uneven plating of lithium metal during charge/discharge process causes serious safety hazards. Here, a carbon-based 3D skeleton (CC@Co-NCNTs) with Co nanocrystals anchored N-containing carbon nanotubes (Co-NCNTs) was constructed to induce the uniform lithium plating towards dendrite-free lithium metal batteries. The Co-NCNTs in the skeleton exhibit enhanced lithophilicity, supplying abundant nucleation sites. Moreover, the ingenious hierarchical structure reconstructs the current density distribution, promoting the uniform lithium plating. Particularly, the electrons from the Co nanocrystals are transferred to the surface of Co-NCNTs, which offers a dynamic charge distribution on the surface of the skeleton along with the plating of lithium ions during the charge-discharge process, thus modulating uniform lithium plating on the Co-NCNTs skeleton. The above-mentioned mechanism is further verified by first-principle calculations and multi-physical field simulation. Thus, the CC@Co-NCNTs@Li symmetric cell presents a long-term cyclic stability (over 1300 h) at a high current density of 40 mA cm −2 . The CC@Co-NCNTs@Li/LiFePO4 cell still delivers a discharge capacity of 135 mAh g −1 at 1 C after 500 cycles. This work provides new insights to the study of functional skeletons for dendrite-free lithium batteries. Graphical Abstract: The 3D skeleton (Composed of carbon cloth (CC), Co nanoparticles and N-containing carbon nanotubes (NCNTs). CC@Co-NCNTs) possesses superior lithophilicity, which is favourable for filling molten lithium. The electrons from the Co nanocrystals are transferred to the surface of Co-NCNTs, which offers a dynamic charge distribution on the surface of the skeleton along with the plating of lithium ions during the charge-discharge process, thus modulating uniform lithium plating on the Co-NCNTs skeleton. Thus enabling realized a 1300-hour cycle life for the Li symmetric cell with a low overpotential. ga1 Highlights: A creative strategy of modulating lithium uniform plating with dynamic charge distribution is proposed. The carbon-based 3D skeleton (CC@Co-NCNTs) with Co nanocrystals anchored N-containing carbon nanotubes is designed. DFT calculations and COMSOL simulation reveal the mechanism for the uniform plating of Li ions on CC@Co-NCNTs. The CC@Co-NCNTs@Li symmetric cell exhibits over 1300 h cycling stability at a high current density of 40 mA cm -2 .